Diffuse large B-cell lymphoma presenting as acute lumbosacral plexopathy with persistent lower back pain and fatigability - Ritwik Ghosh; Moisés León-Ruiz; Abdus S. Mondal; Souvik Dubey; Julián Benito-León (Journal of Family Medicine and Primary Care)
Various types of lymphoma can involve the lumbosacral plexus, mainly diffuse large B-cell lymphoma, in which cancer-related persistent fatigue and fatigability (a new concept that assesses fatigue to specific activities) can occur. We report a rare case of acute right L2-S1 lumbosacral plexopathy secondary to diffuse large B-cell lymphoma, presenting with persistent lower back pain and pronounced fatigability. A 49-year-old male with controlled primary hypothyroidism experienced progressive lower back pain extending to the right lower limb, accompanied by dysesthesias and significant fatigue exacerbated by physical activities. Clinical examination revealed asymmetrical lower limb weakness, an absent right ankle reflex, and a positive straight leg raise test indicative of lumbosacral plexopathy. Comprehensive serological and imaging evaluations, including MRI and 18F-FDG PET-CT, identified lumbosacral spine lesions and widespread lymphomatous involvement. Immunohistochemical analysis confirmed the presence of CD20+, CD10+, bcl2+, bcl6+, and MUM1+ cells, establishing a diagnosis of diffuse large B-cell lymphoma. This case underscores the importance of considering lymphomatous lumbosacral plexopathy in the differential diagnosis of fatigability and lower back pain to prevent misdiagnosis and ensure timely, appropriate treatment. Further studies are suggested to explore the implications of lymphoma on neuropathy and chronic fatigability among survivors.